2016
DOI: 10.1161/hypertensionaha.116.07430
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Impact of ROCK2 on Carotid and Cerebrovascular Function

Abstract: Rho kinase (ROCK) has been implicated in physiological and pathophysiological processes, including regulation of vascular function. ROCK signaling is thought to be a critical contributor to cardiovascular disease, including hypertension and effects of angiotensin II (Ang II). Two isoforms of ROCK (1 and 2) have been identified, and are expressed in vascular cells. In this study, we examined the importance of ROCK2 in relation to vessel function using several models and a novel inhibitor of ROCK2. First, incuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 58 publications
4
40
0
1
Order By: Relevance
“…Thus, we examined effects of Y-27632, which inhibits both ROCK1 and ROCK2 isoforms equally effectively. 22 Y-27632 did not affect vascular responses in non-Tg mice, but restored endothelial function in arteries from E-V290M mice treated with Ang II (Figure 5A). …”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, we examined effects of Y-27632, which inhibits both ROCK1 and ROCK2 isoforms equally effectively. 22 Y-27632 did not affect vascular responses in non-Tg mice, but restored endothelial function in arteries from E-V290M mice treated with Ang II (Figure 5A). …”
Section: Resultsmentioning
confidence: 94%
“…22, 23 Interactions between PPARγ, RhoA (an activator of ROCK), and ROCK has been observed in vascular muscle. 5, 6, 24 Whether similar interactions occur between PPARγ and ROCK in endothelial cells is less clear.…”
Section: Resultsmentioning
confidence: 99%
“…For example, isolated parenchymal arterioles develop greater myogenic tone than the middle cerebral artery. 34, 4750 Small pial arterioles have substantial tone in vivo, 5156 greater than that present in larger vessels within the same network. 57, 58 Through its molecular targets, eNOS influences tone in large arteries to the smallest parenchymal arterioles.…”
Section: Part I Cerebrovascular Disease: the Prelude To Strokementioning
confidence: 99%
“…92 Activation of RhoA and its target ROCK are required for Ang II- and endothelin-1 induced endothelial dysfunction and reduced NVC (Figure 2). 50, 93 Subsequent experiments revealed that the ROCK2 isoform of ROCK was essential for Ang II-induced endothelial dysfunction. 50 …”
Section: Part I Cerebrovascular Disease: the Prelude To Strokementioning
confidence: 99%
See 1 more Smart Citation